2012
DOI: 10.4102/sajhivmed.v13i3.127
|View full text |Cite
|
Sign up to set email alerts
|

TB/HIV integration at primary care level: A quantitative assessment at 3 clinics in Johannesburg, South Africa

Abstract: Background In 2004 the World Health Organization WHO) released the Interim Policy on Collaborative TB/ HIV activities. According to the policy, for people living with HIV (PLWH), activities include intensified case finding, isoniazid preventive therapy (IPT) and infection control. For TB patients, activities included HIV counselling and testing HCT), prevention messages, and cotrimoxazole preventive therapy (CPT), care and support, and antiretroviral therapy ART) for those with HIV-associated TB. While importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(11 reference statements)
0
4
1
Order By: Relevance
“…Correspondingly, Rie et al found that in Ethiopia 85% of TB patients at DOTS clinics were tested for HIV/AIDS [13]. Our result is not in conformity with [12,13] where only 75% of TB patients had their HIV status documented and only a little more than half of TB patients were tested for HIV, respectively.…”
contrasting
confidence: 86%
See 1 more Smart Citation
“…Correspondingly, Rie et al found that in Ethiopia 85% of TB patients at DOTS clinics were tested for HIV/AIDS [13]. Our result is not in conformity with [12,13] where only 75% of TB patients had their HIV status documented and only a little more than half of TB patients were tested for HIV, respectively.…”
contrasting
confidence: 86%
“…A quantitative assessment at 3 clinics in Johannesburg, South Africa, to evaluate TB/HIV integration at the primary care level established that the proportion of clients newly diagnosed with HIV who were screened for TB symptoms could not be determined, because it was not systematically documented [12]. Correspondingly, Rie et al found that in Ethiopia 85% of TB patients at DOTS clinics were tested for HIV/AIDS [13]. Our result is not in conformity with [12,13] where only 75% of TB patients had their HIV status documented and only a little more than half of TB patients were tested for HIV, respectively.…”
mentioning
confidence: 99%
“…Increasing ART coverage is important for both preventing TB and improving TB outcomes [28], and collaborative TB/HIV activities have been recommended as a strategy for national programs [29]. However significant barriers to scale up of these activities persist in South Africa [3033]. For example, routine provision of isoniazid prophylaxis in people living with HIV and rapid initiation of ART among co-infected persons have been identified as the least available TB/HIV services in public medical facilities [33].…”
Section: Discussionmentioning
confidence: 99%
“…lic Health, University of KwaZulu-Natal, Durban, South Africa; 7 HIV Prevention Research Unit, South African Medical Research Council, Durban, South Africa; 8 Medical Research Council, Clinical Trials Unit at University College London (UCL), London, UK; 9 Department of Epidemiology, Mailman School of Public Health, Columbia University, New York, USA…”
Section: O M P E T I N G I N T E R E S T Smentioning
confidence: 99%
“…By 2016, HIV‐TB services were routine care in SA and comprised: early antiretroviral therapy (ART) for TB patients irrespective of CD4 cell count; isoniazid preventive therapy (IPT) for eligible HIV patients; HIV testing services (HTS) for all patients, especially TB patients; TB screening and diagnostic testing [ 5 ]. Evidence has surfaced of patients accessing primary healthcare (PHC) clinics and being missed for HIV and TB services [ 6 , 7 , 8 , 9 ]. Integrated HIV‐TB service delivery requires high‐level organization and planning by clinic teams against a backdrop of large patient numbers and constrained resources [ 6 , 7 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%